Intraoperative OCT Pachymetry in Patients Undergoing Dextran-Free Riboflavin UVA Accelerated Corneal Collagen Crosslinking. (2nd October 2016) - Rechichi, Miguel; Mazzotta, Cosimo; Daya, Sheraz; Mencucci, Rita; Lanza, Michele; Meduri, Alessandro
ABSTRACT: Purpose : To assess intraoperative corneal pachymetry in patients undergoing accelerated corneal collagen crosslinking with a dextran-free riboflavin solution. Methods : Prospective, non-comparative, multicenter interventional study. Thirty patients with progressive keratoconus were enrolled in the study from the Siena Crosslinking Center™ in Siena, Italy and the Eye Center in Catanzaro, Italy. The mean age was 26.9 ± 6.5 years. Patients underwent pulsed light accelerated crosslinking (PL-ACXL) by KXL I UV-A source (Avedro Inc., Waltham, MS, USA) with 8 min (1 s on/1 s off) of UV-A exposure, 30 mW/cm 2 and an energy dose of 7.2 J/cm 2 . Corneal stroma was soaked with a dextran-free 0.1% riboflavin solution plus hydroxyl-propyl methylcellulose (HPMC) (VibeX Rapid, Avedro). Intraoperative corneal thickness was preoperatively (PRE-OP) evaluated by corneal optical coherence tomography (iVUE Optovue Inc., Fremont, CA, USA) after epithelium removal (EPI-R), after 10 min of riboflavin soaking (RS) and after UV-A irradiation (IR). Statistical analysis was conducted using a Wilcoxon test and SPSS v16.0. A p -value of <0.05 was considered to be statistically significant. Results : Average PRE-OP central corneal thickness (CCT) and thinnest corneal thickness (TCT) were 437.3 ± 36.9 and 418.9 ± 28.8 μm, respectively. Average EPI-R CCT and TCT values were 388.5 ± 36.8 and 381.5 ± 36.61 μm, respectively. Average CCT and TCT values after 10 min RS were 385.2 ± 37.8 and 380.6 ± 36.7 μm, respectively. The final average CCT and TCT values after IR were 379.4 ± 37.2 and 378.1 ± 36.4 μm, respectively. Conclusions : The study demonstrated a non-statistically significant intraoperative corneal thickness reduction in patients undergoing PL-ACXL corneal collagen crosslinking by using dextran free HPMC 0.1% riboflavin solution.